Effect Of Formulation On The Fluffiness And Volume Of A Commercial Cake Premix In Relation To Its Acceptability - Fredy, Crispin-Sanchez; Medina, Wenceslao T.; Gordillo, Oscar Amado Crisóstomo; Sánchez, Ivan Crispin; Castilla, Nils Leander Huamán; Chire-Fajardo, Gabriela; Peralta, Milber Oswaldo Ureña (Migration Letters, 2024)
Making a commercial cake based on a premix is a matter of finding the balance of key ingredients that influence the uniform distribution and homogeneous size of the pockets in order to obtain an acceptable commercial sponginess in a premix. The objective of this work was to evaluate the formulation of a commercial premix in relation to its fluffiness and volume employing image analysis and its acceptability. Initially, a screening was performed with Taguchi’s methodology evaluating statistical descriptors of texture by image analysis and volume. The sponginess was evaluated by means of the statistical descriptors of texture ASM, contrast, IDM, and entropy determined by the GLCM method. Two optimum formulations were obtained, formula A consisting of monoglyceride, egg, oil, sugar, xanthan gum, and baking powder, the values of 4.0, 80.0, 50.0, 70.0, 0.05, and 2.0 percent respectively, and formula B; monoglyceride, egg, oil, sugar, xanthan gum, and baking powder; the values of 7.0, 80.0, 30.0, 70.0, 0.05 and 5.0 percent respectively, which were subjected to an acceptability test with 80 consumers. In the result, according to the statistic t = 0.375858 > α (significance level=0.05), the null hypothesis is rejected and the alternative hypothesis is accepted, which means that there is no statistically significant difference between formulas A and B for consumers. This means that, in a cake, not only the volume is important, but also its sponginess (the latter is due to the correct size, distribution, and dispersion of alveoli, as well as its homogeneity in all the cut surface of the crumb of the cake).